Effect of financial development and technological innovation on green growth—analysis based on spatial Durbin model - Cao, Jianhong; Siong, Hook Law; Abdul Samad, Abdul Rahim; W Mohamad, Wan Norhidayah; Wang, Jianlong; Yang, Xiaodong (Elsevier, 2022)
This research examines the spatial effect of financial development and technological innovation on green growth in China using the Spatial Durbin Model (SDM) based on the 30 provinces’ panel data from 2011 to 2018. The green growth index is measured by using Entropy Weight Method (EWM). The results show that: First, the development scale of financial institutions (lnFDS) in the local province has a significantly negative effect on local green growth (GG), but has a significantly positive effect on green growth (GG) in the surrounding provinces. Second, the scale of the stock market in the local province (lnSTO) has a significantly positive effect on green growth both in the local and surrounding provinces. Third, technological innovation (lnTI) in the local province has a significantly positive effect on local green growth, while it has an insignificantly positive effect on green growth in the surrounding provinces. Fourth, the interaction between financial development and technological innovation increases the negative effect on green growth, which indicates that the integration efficiency of financial development and technological innovation is not high. Lack of institutional innovation and insufficient financial support for technological innovation in the financial sector may be one of the important reasons.